Quality Analysis of Milk in Kathmandu Valley - Parajuli, Astha; Rimal, Prasiddhi; Maharjan, Rujisha; Chaudhary, Richa; Chaturwedi, Shashi Bhusan (Tribhuvan University Journal of Microbiology, 2018)
Objectives: This study was carried out to evaluate physiochemical, adulteration and microbial quality of milk sold in Kathmandu Valley. Methods: The study was carried out in Microbiology Laboratory of DAV College. The total of 20 milk samples randomly collected from different places of the valley including 10 pasteurized milk sample and 10 were raw milk sample, were processed for Physiochemical and Microbiological analysis. Result: The laboratory analysis revealed that the pasteurized samples has less mesophilic count as well as coliform count than raw milk samples. About 55% milk samples showed neutralizer test positive and 10% of milk samples were found to be positive for sugar test. However, none of the samples were found to contain starch as an adulterant. The average fat content of milk samples of Kathmandu Valley was 3%. Fat percent was significantly different among different sources of sampling points. The highest milk fat content value was recorded at Pulchowk (3.7%). The average SNF of Kathmandu Valley was 7% in which the pasteurized sample had the highest average SNF (7.3%) and the raw milk had lowest average SNF (6.8%). Conclusion: The significant variation in the physiochemical properties and microbial properties of the milk samples showed that people should be conscious about the consumption of market milk.